If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 5w = 0 Solving 5m + 5w = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5w' to each side of the equation. 5m + 5w + -5w = 0 + -5w Combine like terms: 5w + -5w = 0 5m + 0 = 0 + -5w 5m = 0 + -5w Remove the zero: 5m = -5w Divide each side by '5'. m = -1w Simplifying m = -1w
| x+50=60 | | x-35=54 | | 6y=-12x-36 | | 3a-4=7 | | 9v-4=2v+45 | | -3a-2+5=2a-8 | | 5/9x+2=-7 | | 3/5x+7=-2 | | 6r-14=r+1 | | 16x^2-35x+18=0 | | 5+5p=26+2p | | 16x^2-35x+15=0 | | 4k-2=16-2k | | 5g-1=2g+20 | | 5c+3=3c+9 | | 24+x=4x | | 2x+4x=9 | | X+40=5x | | 35*6= | | 5x-4y-11y+3x+9= | | 64-15x+x^2=0 | | 24q+3456=-2q^2 | | 2x^2+95x+16=0 | | x-y+z=455 | | 1/3x+1/4x=7 | | x/3+2=2x/5-3 | | 4x-8=49 | | 24q+3456=2q^2 | | 3(x-2)+7=4(x+1)-2 | | 5x+2=6x^2+7x-3 | | 30x-1=0 | | 2x-21=-23 |